Injection Reactions after Administration of Sustained-release Meloxicam to BALB/cJ, C57BL/6J, and Crl:CD1(ICR) Mice - Fuetsch, Stephanie R (J Am Assoc Lab Anim Sci, 2021)
The sustained-release formulation of meloxicam (MSR) is a compounded NSAID that may provide pain relief for as long as 72 h after administration. MSR injection-site skin reactions have occurred in several species but have not previously been observed in mice. We investigated the development and progression of localized skin reactions after a single injection of MSR in Crl:CD1(ICR), C57BL/6J, and BALB/cJ mice. Each mouse received a subcutaneous injection of MSR (n = 60), standard-formulation meloxicam (MEL; n = 24) or saline (control; SC; n = 24) and was scored daily according to a 5-point system for erythema and mass characteristics. Mice were euthanized at either 7 or 14 d after injection and underwent postmortem analysis. MSR-treated mice had more erythematous and mass reactions than did MEL and SC mice. Mass lesions developed in 49 MSR mice (82%; 95% CI, 70% to 90%), 5 MEL animals (21%; 95% CI, 7% to 42%), and 1 SC mouse. MSR-treated BALB/cJ developed erythematous lesions less frequently than similarly treated Crl:CD1(ICR) or C57BL/6J. Lesions often were ventrolateral to the injection site. The median times to the appearance of mass and erythematous lesions were 2 d and 3 d, respectively. Histologically, the erythematous and mass reactions correlated with necrotizing to pyogranulomatous injection-site panniculitis. Inflammation severity scores at 7 and 14 d after injection were greater in the MSR-treated group than the other 2 groups. No strain- or sex-associated differences emerged except that inflammation severity scores at day 14 were higher in Crl:CD1(ICR) females than males. The character of the inflammatory response in MSR-treated mice did not differ between 7 and 14 d after injection, indicating that MSR-induced inflammation is slow to resolve. The ventral migration and delayed onset of MSR injection-site reactions could result in their being attributed to another cause or not being identified. Researchers and clinicians should be aware of the potential for slowly resolving injection-site reactions with MSR.